2021
DOI: 10.7759/cureus.18828
|View full text |Cite
|
Sign up to set email alerts
|

Role of Laparoscopy in the Surgical Management of Acute Small Bowel Obstruction: Fact or Fiction?

Abstract: Background: Laparotomy (open surgery) is considered the standard approach for acute small bowel obstruction (ASBO). However, with the advent of minimally invasive surgery, the laparoscopic approach is gaining popularity. There is no consensus on the appropriate setting for laparoscopic therapy for small bowel obstruction (SBO).Aim and objectives: The purpose of this study is to evaluate the outcomes of laparoscopic surgery for ASBO.Patients and methods: We retrospectively evaluated the prospectively collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…Previous studies have shown that the laparoscopic technique accelerates the postoperative recovery process. [ 19 ] In our study, the selection of laparoscopic surgery shortened the hospital stay by approximately 5 days. Some previous studies have reported that laparoscopy shortened hospital stay by 1 day [ 15 ] and some others by 3 to 4 days.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have shown that the laparoscopic technique accelerates the postoperative recovery process. [ 19 ] In our study, the selection of laparoscopic surgery shortened the hospital stay by approximately 5 days. Some previous studies have reported that laparoscopy shortened hospital stay by 1 day [ 15 ] and some others by 3 to 4 days.…”
Section: Discussionmentioning
confidence: 72%
“…Although the laparoscopic method is becoming more and more well-liked as minimally invasive surgery, there is no consensus on the appropriate setting for laparoscopic therapy for small bowel obstruction. 21,22 In conclusion, however, intussusception is a rare cause of abdominal pain in adults, it is a diagnosis to consider in patients who have nonspecific abdominal pain because it can be a sign of cancer. In all situations where suspicion exists, emergency physicians should seek early surgical consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the laparoscopic method is becoming more and more well‐liked as minimally invasive surgery, there is no consensus on the appropriate setting for laparoscopic therapy for small bowel obstruction. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ngược lại, thời gian biểu hiện bệnh có sự khác biệt nhưng không có ý nghĩa thống kê. Nghiên cứu của Farinella và nghiên cứu của Harvitkar cho rằng, mổ bụng > 2 lần được xem là chống chỉ định tương đối với phẫu thuật nội soi do dính nhiều gây khó khăn khi đặt Trocar đầu tiên [6,7].…”
Section: Bàn Luậnunclassified